Characterisation of tualang honey silver nanoparticles (THSN) and neuroprotective effect of tualang Honey and thsn on kainic acid-induced neurodegeneration in male rats’ hippocampus - Hasim, Hidani (2023)
Neurodegeneration is a feature of many chronic disorders of the central nervous system that result in the deterioration of neuronal structure and function. Experimental induction of excitotoxicity-mediated neurodegeneration by kainic acid (KA) has been associated with various mechanisms, including oxidative stress, excessive inflammatory response, and apoptosis. Tualang honey (TH), which contains a powerful natural antioxidant, is increasingly studied as an alternative prevention for several neurodegenerative diseases. Despite the numerous studies highlighting the benefits of TH, the application of silver nanoparticles synthesised from TH remains limited. Thus, this research aimed to evaluate the neuroprotective effects of TH and TH silver nanoparticles (THSN) against KA-induced neurodegeneration in the rat hippocampus. THSN was synthesised and characterised by UV-Visible (UV-Vis) spectroscopy, X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, Field Emission Scanning Electron Microscope (FESEM), and Transmission Electron Microscope (TEM). A total of 288 male Sprague Dawley rats were randomised into three experimental phases (including behavioural assessment, biochemical measurement, and histological studies). In each phase, 96 rats were randomly divided into eight major groups (n = 12/major group): control, THSN 10 mg, THSN 50 mg, KA only, KA + TH, KA + THSN 10 mg, KA + THSN 50 mg, and KA + Topiramate (TPM). Each major group was subdivided into 24h and five days subgroups, comprising 16 subgroups (n = 6/subgroups). The rats were given distilled water, TH (1.0 g/kg), THSN (10 mg/kg or 50 mg/kg), or TPM (40 mg/kg) orally, five times at 12 h intervals. Subcutaneous injections of saline solution or KA (15 mg/kg) were given 30 min after the last oral treatments. Before the animals were euthanised, behavioural assessments were conducted using the open field test and a novel object recognition test. Biochemical, toxicological, and histological analyses were performed on the hippocampus at 24 h and 5 days following KA induction. The KA administration on rats resulted in seizures, alteration in locomotor activity, and memory impairment. Additionally, KA increased oxidative stress (as evidenced by significant increases in MDA, PCO, and NOx levels and significant decreases in CAT, SOD, GSH and TAS levels), TNF-α level (neuroinflammatory marker), caspase-3 activity (apoptosis marker), and subsequent neurodegeneration in the hippocampus. The result for renal and liver function test showed that THSN caused no significant toxic effect on animals. Notably, TH and THSN pre-treatment increased the seizure latency, improved memory deficits, and reduced oxidative stress, neuroinflammation, apoptosis, and neuronal damage of rats’ hippocampus in the KA-induced neurodegeneration model. In conclusion, TH and THSN exerted their neuroprotective effects against KA-induced neurodegeneration via antioxidant, anti-inflammatory, and anti-apoptotic properties. Further clinical studies need to be conducted to establish TH and THSN as a potential neuroprotective agent.